Implementasi Layanan Khusus UKS (Usaha Kesehatan Sekolah) pada Indikator Pendidikan Kesehatan di SMA Kota Jayapura - Juniasti, Helen Try; Tijow, Meylani Aljeinie (NOKEN : Jurnal Pengelolaan Pendidikan, 2024)
The UKS (school health business) program should be a catalyst forr improving the health statu of school-age children so that it can be encourage improvements in the quality of education and learning achivment of students by implementating PHBS (clean and healthy living behavior).objective : to identify the implementation of UKS special service program on health education indicators. Method this research uses a survey research design with a quantitative descriptive approach. Data collection used the UKS/M stratification instrument for high school level. Data were analyzed using univariate analysis referring to the UKS/M SMA stratification indicators with the categories minimum, standard, optimal and complate. The research sample of 25 included public and private high schools in the jayapura city area. The research results showed that the implementation of special UKS high school services throuhout jayapura city was based on the UKS stratification of the majority of health education indicators in the standard strata. The conclusion in that the implementation of special UKS high school services throuhoutJayapura City on health education indicatorssow that the category is not good.